Pocket guide to mycological diagnosis - De Aguiar Cordeiro, Rossana (Boca Raton : CRC Press, 2020)
"The Pocket Guide to Mycological Diagnosis aims to provide useful and concise information for microbiologists and professionals interested in the diagnosis of the most relevant fungal species of medical importance. This book will allow mycologists to face the emergoing challenges of routine diagnosis"--
OCLC-licensed vendor bibliographic record.
Keywords: Medical mycology; Pathogenic fungi; MEDICAL / Infectious Diseases; SCIENCE / Life Sciences / Biology / Microbiology; SCIENCE / Microscopes & Microscopy